Single-cell RNA sequencing reveals distinct transcriptional features of the purinergic signaling in mouse trigeminal ganglion - Jia, Shilin; Liu, JinYue; Chu, Yanhao; Liu, Qing; Mai, Lijia; Fan, Wenguo (Frontiers in Molecular Neuroscience, 2022)
Trigeminal ganglion (TG) is the first station of sensory pathways in the orofacial region. The TG neurons communicate with satellite glial cells (SGCs), macrophages and other cells forming a functional unit that is responsible for processing of orofacial sensory information. Purinergic signaling, one of the most widespread autocrine and paracrine pathways, plays a crucial role in intercellular communication. The multidirectional action of purinergic signaling in different cell types contributes to the neuromodulation and orofacial sensation. To fully understand the purinergic signaling in these processes, it is essential to determine the shared and unique expression patterns of genes associated with purinergic signaling in different cell types. Here, we performed single-cell RNA sequencing of 22,969 cells isolated from normal mouse TGs. We identified 18 distinct cell populations, including 6 neuron subpopulations, 3 glial subpopulations, 7 immune cell subpopulations, fibroblasts, and endothelial cells. We also revealed the transcriptional features of genes associated with purinergic signaling, including purinergic receptors, extracellular adenosine triphosphate (eATP) release channels, eATP metabolism-associated enzymes, and eATP transporters) in each cell type. Our results have important implications for understanding and predicting the cell type-specific roles of the purinergic signaling in orofacial signal processing in the trigeminal primary sensory system.